Caregiver Influences on Eating Behaviors in Young Children: A Scientific Statement From the American Heart Association. Issue 10 (18th May 2020) - Wood, Alexis C.; Blissett, Jacqueline M.; Brunstrom, Jeffrey M.; Carnell, Susan; Faith, Myles S.; Fisher, Jennifer O.; Hayman, Laura L.; Khalsa, Amrik Singh; Hughes, Sheryl O.; Miller, Alison L.; Momin, Shabnam R.; Welsh, Jean A.; et al.
Abstract: A substantial body of research suggests that efforts to prevent pediatric obesity may benefit from targeting not just what a child eats, but how they eat. Specifically, child obesity prevention should include a component that addresses reasons why children have differing abilities to start and stop eating in response to internal cues of hunger and satiety, a construct known as eating self‐regulation . This review summarizes current knowledge regarding how caregivers can be an important influence on children's eating self‐regulation during early childhood. First, we discuss the evidence supporting an association between caregiver feeding and child eating self‐regulation. Second, we discuss what implications the current evidence has for actions caregivers may be able to take to support children's eating self‐regulation. Finally, we consider the broader social, economic, and cultural context around the feeding environment relationship and how this intersects with the implementation of any actions. As far as we are aware, this is the first American Heart Association (AHA) scientific statement to focus on a psychobehavioral approach to reducing obesity risk in young children. It is anticipated that the timely information provided in this review can be used not only by caregivers within the immediate and extended family but also by a broad range of community‐based care providers.